Proportional-Derivative Linear Quadratic Regulator Controller Design For Improved Directional And Lateral Motion Control Of Unmanned Aerial Vehicles - Yap, Kai Wen (Universiti Sains Malaysia, 2019)
This study investigates the directional and lateral motion control of unmanned aerial vehicles by controlling the sideslip angle through a simulation in MATLAB/Simulink. The linear model of a mini unmanned aerial vehicle, Ultra Stick 25e is applied to controllers to explicate the lateral-directional motion of the unmanned aerial vehicle. Directional and lateral motion control of an unmanned aerial vehicle is very crucial especially when the unmanned aerial vehicle performs any maneuver. These maneuvers usually performed when the unmanned aerial vehicle is avoiding any flying obstacles or in tasks that require complex maneuvers. It is crucial for an unmanned aerial vehicle to have the ideal performance to achieve the desired response instantly with 100% precision especially when the unmanned aerial vehicle is avoiding flying obstacles. However, currently available controllers show a delay in the response time which need further improvements. Therefore, a proportional-derivative linear quadratic regulator controller is developed and compared with a proportional-integral-derivative controller, a linear quadratic regulator controller, and a proportional linear quadratic regulator controller. The flight condition of the mini unmanned aerial vehicle model was set at forward velocity, u=17m/s, pitch angle, θ= 0.0217rad, elevator deflection angle, η = 0.091rad, throttle angle, τ = 0.559rad, aileron and rudder deflections of ξ= 0rad, ζ= 0rad respectively, and altitude of 120m. The proportional-integral-derivative controller, linear quadratic regulator controller, proportional linear quadratic regulator controller, and proportional-derivative linear quadratic regulator controller are simulated in MATLAB/Simulink and compared with the results in terms of rise time, settling time, overshoot, steady-state error and root mean square error. The tuning of each controller makes sure every controller performs at its optimized state which gives the best performance for each controller. The proportional-derivative linear quadratic regulator controller enhances the response of the system by reducing the settling time by more than 74% compared with other controllers. The rise time and steady-state error are improved by more than 50% whereas the root mean square error is improved by more than 6% and having the overshoot at a reasonable value.